The Effect of Green Marketing on Product Purchasing Decisions with E-Wom as a Mediating Variable - Romadhany, Yoga Itsna; Hakim, Lukman (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Marketing communications in this modern era has experienced very significant developments. The increasingly advanced development of the times demands that everything must change in such a way, keeping up with current developments in the field of marketing communications. The aim of this research is to analyze the influence of Green Marketing on Garnier product purchasing decisions in Surakarta with E-Wom as an intervening variable. This type of research is quantitative research. The population of this research is Garnier product users in Surakarta. This research uses primary data. So the minimum sample that researchers can take is 100 respondents. Sampling technique in this research. using purposive sampling. This research uses SMARTPLS 3.0 software. This research uses Structural Equation Model (SEM) analysis with Partial Least Square (PLS). The results of this research are that Green Marketing has a positive and significant influence on Purchasing Decisions. Green Marketing has a positive and significant influence on E-WOM. E-WOM has a positive and significant influence on purchasing decisions. E-WOM can mediate the relationship between Green Marketing and Purchasing Decisions.